The Inextricability of Art, Religion and Politics in Iraq. (1st January 2018) - Baram, Halgurd A.
Abstract : Artist Halgurd A. Baram reflects on two of his own works of art, "Iraqi Flag" and "Militarizing the Word of God, " which were presented in the show Catalyst and which sought to explore and expose the cultural and political meanings embedded in the iconic aspects of Islamic calligraphy and its relationship to Arabic language. Baram's exploration goes beyond a simple understanding of the Arabic alphabet as being essential to calligraphy and linked to religious notions in order to uncover the other meanings that are brought to the Arabic language in its written form. This essay goes on to explore how the Arabic language has become intimately affiliated with Islam as a religion, to the extent that they are an inseparable unity, and how this relationship potentially impacts national identity, particularly for non-Arab Muslims.